DESAIN DAN PENGEMBANGAN POJOK LITERASI DAN PELATIHAN SOSIAL MEDIA PADA RT. 62 KELURAHAN GRAHA INDAH - Kumalaningrum, Amalia Nur; Winarni; Adhitya, Sayid Rifqy; Putri, Sabrina Aulia; Siagian, Joel Parulian Apriadi; Immanuel, Legi Raymond; Panjaitan, Shindi Claudia; Manik, Anriyani; Tari, Sarnita; Dewi, Rachel Glory Julyana (Universitas Mataram, 2024)
Community service is an activity involving universities and the community to improve the standard of living and knowledge of the community. Kampoeng FABA in Graha Indah Village RT 62, North Balikpapan, is one of the areas that requires special attention in this program. Based on the survey results, it was found that the Kampoeng FABA environment is diverse and developing, but faces the problem of low interest in reading for children and the ability of residents to manage social media. The purpose of this activity was to significantly increase children's interest in reading and to reduce the influence of dependence on the use of gadgets. This activity also aimed to strengthen the ability of residents to manage Kampoeng FABA social media, thereby creating an environment that supported digital skills. There were two main programs in this activity, namely the development and design of literacy corners and social media management training. The development of literacy corners was carried out by providing books and tools to support children's literacy. The training was performed with two themes, namely training on the use of Instagram and design training with Canva. The results of this activity were realized with the formation of a literacy corner that provides a variety of children's books and the holding of educational competitions for children as a stimulus for reading culture and socialization of literacy corners. Instagram and Canva training activities could improve residents' knowledge and skills in utilizing social media accounts. Evaluation of participants' understanding of social media showed an increase of 25% after participating in the training. The results of the participant satisfaction questionnaire showed that 100% of training participants gave a positive response that this training helped improve understanding of the use of social media and the material presented was very useful. The development of literacy corners and social media training could support increasing children's interest in reading and strengthen the ability of Kampoeng FABA residents to utilize social media more productively.